Genetic diversity of Senepol cattle in Colombia using ten multiplexed microsatellites (2016)
ABSTRACT: An automated multiplex PCR assay of 10 polymorphic microsatellite loci was optimized here in Senepol bovine cattle. Allele frequencies were estimated for Colombian herds. The power of this set of markers for parentage and kinship analyses was also tested. Population genetic parameters, combined probability of identity (CPI) and combined probabilities of exclusion (CPE) were estimated. The average number of alleles per locus was 14, the effective number of alleles was 5, the observed and expected heterozygosities were 0.635 and 0.776, respectively, the Shannon Index was 2.70 and the polymorphic information content was 0.751. These values evidenced elevated levels of polymorphism and an underestimation of genetic diversity through the use of manual genotyping methods. Inbreeding coefficient (Fis=0.206) in Colombian Senepol herds was moderate. Altogether, data from the used set of microsatellite loci yielded a CPI between two random samples of 1.07E-12. The CPE in parentage testing were >0.998 for the first parent and >0.999 for both the second parent and parent pairs. This set of polymorphic markers can be genotyped in a relatively easy, effective and reliable way for relatedness and forensic analyses. Finally, we recommend our approach for population genetic analyses of other Senepol populations and future genetic monitoring of inbreeding in Senepol herds.